Women’s Exploitation in the Word of Work : Criminology Study and Human Right Protection (Pimp Case Study in Sragen) - Devindya Citra; Indah Sri Utari (Law Research Review Quarterly, 2025)
Exploitation of women in the workplace through prostitution practices still occurs in Sragen Regency and places women in a vulnerable position without adequate legal protection. This study aims to analyse the forms of exploitation of women and the role of pimps in prostitution practices in Sragen from a criminological perspevtive, as well as examine the implementation of Law Number 21 og 2007 in handling cases and protecting victims. This study uses a normative research method with a legislative approach and cases studies. The results of the study indicate the exploitation is carried out systematically through fraud, forced sexual services, retrictions on freedom, as well as threats and violence, which fulfil the elements of forced labor and the crime of human trafficking.